(untitled) (Scientific journal of the Fergana State University, 2026)
this article examines the concept of a generalizing lesson in the elementary grades, its goals and significance. Generalizing classes provide students with the opportunity to combine the knowledge they have learned, analyze and form new knowledge. The main goals of the classes are: to generalize knowledge, develop critical thinking, improve practical skills, self-assessment, Solve Problem tasks and develop communication skills. Generalizing classes help strengthen students ’ logical thinking and social skills, providing an important foundation for their future success.